Implementasi Kurikulum 2013 di Sekolah Dasar bagi Perkembangan Peserta Didik di SDN Sukasari 4 - Ina Magdalena; Diah Vitaloka; Elismawati Elismawati; Khaerina Mita Sasmita Aji; Silmi Rufaidah (Jurnal Halaqah, 2020)
This study aims to describe how the curriculum has been implemented in schools, teaching materials used in supporting the implementation of the 2013 curriculum, assessments, facilities and infrastructure that support the implementation of the 2013 curriculum, and find out curriculum implementation factors. The studies used a qualitative exploratory approach, data collection was done by observation and interviews. The results of this study that there are many factors that affect the curriculum and the role of teachers in implementing the 2013 curriculum at SDN Sukasari 4, Tangerang City.